2022
DOI: 10.1186/s13229-022-00528-z
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent changes in hippocampal spatial activity and hippocampal circuit function are disrupted in a rat model of Fragile X Syndrome

Abstract: Background Fragile X syndrome (FXS) is a common single gene cause of intellectual disability and autism spectrum disorder. Cognitive inflexibility is one of the hallmarks of FXS with affected individuals showing extreme difficulty adapting to novel or complex situations. To explore the neural correlates of this cognitive inflexibility, we used a rat model of FXS (Fmr1−/y). Methods We recorded from the CA1 in Fmr1−/y and WT littermates over six 10-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 113 publications
1
4
0
Order By: Relevance
“…A main neurophysiological correlate of FXS is an alteration of E-I balance towards excitation [11,12]. In keeping with previous observations [88][89][90][91][92][93][94], we report that loss of FMRP is accompanied by increased excitability of the hippocampal network. Additionally, it is widely thought that a crucial determining factor in the FXS-associated increase of the E-I ratio is the reduction in inhibition [95,96].…”
Section: Discussionsupporting
confidence: 91%
“…A main neurophysiological correlate of FXS is an alteration of E-I balance towards excitation [11,12]. In keeping with previous observations [88][89][90][91][92][93][94], we report that loss of FMRP is accompanied by increased excitability of the hippocampal network. Additionally, it is widely thought that a crucial determining factor in the FXS-associated increase of the E-I ratio is the reduction in inhibition [95,96].…”
Section: Discussionsupporting
confidence: 91%
“…Lu et al (Lu et al, 2016) used both 2-photon calcium imaging and in vivo electrophysiology to establish that while CA1 pyramidal cells in the KO mice are overall less active, they showed a significant increase in synchronous activity, which interestingly could be rescued by deep brain stimulation of the fornix. A second study employing high-density tetrode recording in the CA1 region (Kee et al, 2018) found that, like what was reported in the Fmr1-KO rats (Asiminas et al, 2022), place fields in the KO mice failed to show experience-dependent improvements in the spatial coding. Interestingly, the authors also observed the hypersynchronous activity in these mice extended to the SWR events, perhaps occluding learning-dependent consolidation mechanisms necessary for place field refinement.…”
Section: Hippocampal Neural Circuit Activity In Asd Model Micementioning
confidence: 57%
“…More recently (Asiminas et al, 2022) Asiminas et al reported the first in vivo recordings from the hippocampus of a rat model of FXS. They observed while place fields in a novel environment were similar between control and Fmr1-KO rats, the FXS-model animals failed to show experience-dependent improvements in spatial coding when returned to the context the following day.…”
Section: Hippocampal Neural Circuit Activity In Asd Model Micementioning
confidence: 99%
“…This approach has a significant benefit in that you can measure both functional and structural correlates of spine density in the same cells from the same animal. Combining these recordings with pharmacological blockage of voltage-gated sodium channels using tetrodotoxin allows for determination of the quantal synaptic properties of a given neuron . These can then be combined with methods, such as two-photon glutamate uncaging, to measure the activity of individual identified dendritic spines, and super-resolution imaging .…”
Section: Interpretive Considerations For Image Analysis Datamentioning
confidence: 99%
“…Combining these recordings with pharmacological blockage of voltage-gated sodium channels using tetrodotoxin allows for determination of the quantal synaptic properties of a given neuron. 100 These can then be combined with methods, such as two-photon glutamate uncaging, to measure the activity of individual identified dendritic spines, and super-resolution imaging. 55 While this latter study may be the extreme end of functional analysis, further studies have shown the importance of correlating spine structure and function.…”
Section: Analysis Datamentioning
confidence: 99%